BEBERAPA FAKTOR YANG MEMPENG ARUHIMIGRASI TENAGA KERJA INDONESIA (TKI) KE LUAR NEGERI - Waridin Waridin (Muhammadiyah University Press, 2002)
The difference of economic conditions and job opportunities inter countries can be one of the causes why manpower migration to the socially and economically beneficial countries happens. This research is aimed at analyzing some factors, which effect TKI (Indonesian Man Power) migration to foreign countries. Beside, this study is also aimed at analyzing the migration patterns of Indonesian Man Power to work abroad. The sampling method is carried out with multi stage, namely according to the Job groups power working in target countries. To analyze the factors which effect why Indonesian manpower migrates and works abroad is used